Mediastinal hematoma following transradial percutaneous coronary intervention: case report and literature review - Qiangsong Jin; Jiamin Wang; Xiaogang Hu; Xianqing Hu; Shenwen Fu (Frontiers in Cardiovascular Medicine)
Mediastinal hematoma due to transradial PCI is rare. We reported a case of chest tightness, dyspnea, progressive neck swelling after transradial PCI. Clinical examinations such as chest computer tomography were completed and identified as mediastinal hematoma caused by a rupture of the subclavian artery branch and occlude the artery under digital subtraction angiography guidance, the artery was considered to be a collateral vessel of non-bronchial arterial circulation. This case highlights the necessity of exercising extreme caution when utilizing hydrophilic-coated curved-tip guidewires during the advancement process in peripheral vascular procedures. Mediastinal hematoma is a life-threatening complication and progresses rapidly, we need timely identification and diagnosis based on symptoms and appropriate clinical examination, interventional embolization therapy is critical for patients with poor response of conservative treatment.